Consumer Protection on Indonesian Act Number 8 of 1999 (Thematic Review and Perceptions) | حماية المستهلكين في القانون الإندونيسي رقم 8 سنة 1999؛(مراجعة وتصورات موضوعية) - Ina Purwanti (Al-Zahra : Journal for Islamic and Arabic Studies, 2018)
This article aims to analyze reading in consumer law that is the duties and responsibilities of product owners that consumers should know. It also aims at presenting objective perceptions of this law. This article is based on critical analytical approaches. The main source of this article is the text of the Republic of Indonesia Act number 8 of 1999 on consumer protection. Secondary sources are research and studies dealing with this issue. One of the highlights of this article is to review and reflect on the concern about consumer protection and regulation to achieve the interests of consumers in the first place, by activating all existing elements: from the community and civil institutions to the government through the minister concerned. The Consumer Protection Act must be based on several principles and principles called liability principles that eventually lead to consumer rights.